PENGARUH PRINSIP-PRINSIP GOOD GOVERNANCE TERHADAP KUALITAS PELAYANAN PUBLIK DI KANTOR DESA TEGALREJO - Wendi aji saputra (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2024)
The purpose of this study was to determine the effect of the Principles of Good Governance on the Quality of Public Services at the Tegalrejo Village Office. The method used in this research uses descriptive quantitative research with survey research methods. In this study, the population taken was the Tegalrejo Village community with a total population of 458. To determine the number of samples in this study using the Slovin formula with a sample size of 214 respondents. The results of the study showed a significant influence between the principles of good governance on the quality of public services at the Tegalrejo Village Office. This is obtained from the t-test where t_count = 23.838 is greater than t_ (table) = 1.971 and sig value. 0.000 and the coefficient of determination obtained a value of 0.728 or 72.8%, which means that the quality of public services in the Tegalrejo village office is influenced by the principles of good governance by 72.8%.